Commercialized Gospel: A missiological assessment of Prosperity Gospel - Gbote, Eric Z. M. (University of Pretoria, 2013)
The question this paper attempts to answer is: “Does God base his blessings to church members solely on giving”. The research investigated prosperity gospel from a missiological perspective, a gospel that promises material wealth, health and happiness to faithful Christians who sow “faithful seed to the ministers”. A Collection of literatures relating to the subject matter coupled with citations from interviewees was reviewed and analysed, in making judgment in answering the research question. To accomplish the objective of the study the biblical foundation of giving and prosperity were examined, the background, history and synonymous features to prosperity gospel were evaluated, coupled with the views of respondents. A comparison was made, and a conclusion was reached, based on the findings. Thus, grounded on the result obtained from the research the researcher attempts to establish that though God blesses humanity for obeying his command to give, it does not mean that giving is his prerequisite of blessing humankind. The claim that God wants everyone to be rich contradicts the Bible. For no one can instruct God on who to bless and curse, therefore the claim that man of Rhema can decree blessing on humankind per our giving power is unbiblical.
free